The Influence of Servant Leadership Style and Ethical Leadership on Organizational Change - Haidarravy, Saqif; Ismail, Iriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The significance of human resources in determining a company's success renders them a pivotal component in the everyday operations of the organization. Furthermore, the status of this entity is unaffected by external factors, including advanced technological advancements, so rendering it immune to prohibition. This may be attributed to the primary goals of enhancing regulatory frameworks, optimizing decision-making processes, and promoting policy facilitation. The primary objective of this study is to investigate and evaluate the impact of servant leadership and ethical leadership on organizational transformation within the context of Travel An-Namira Madura. All individuals included in this study were employed by the same business. The present study employs a quantitative methodology, using questionnaires sent to a sample of 52 individuals employed in the workforce. The data was processed using the IBM SPSS 25.0 software. The study results indicate that the implementation of servant leadership has a positive influence on the effectiveness of organizational transformation